The Role of Emotional Schemas in Binge Eating and Bedtime Procrastination - Magda Ghassan Fathy; Khaled Jamal Mandoob (Iranian Journal of Psychiatry)
Objective: Given the increasing prevalence of binge eating disorder (BED) and bedtime procrastination (BP) among university students, as well as the notable absence of validated Arabic instruments to assess these behaviors, this study aimed to investigate the role of emotional schemas in BED and BP among university students. By examining these emotional schemas, the study sought to shed light on a potential shared underlying mechanism contributing to both BED and BP, and to adapt and validate the Bedtime Procrastination Scale (BPS) for Arabic-speaking populations. Method: Three samples of Iraqi university students were recruited. The first sample (n = 835) was used for the validation of the Arabic version of the BPS. The second sample (n = 58) was utilized for convergent validity testing, and the third sample (n = 490) was examined for exploring the associations between emotional schemas, BED, and BP. Results: Analyses revealed that maladaptive emotional schemas—particularly devalued, non-acceptance of feelings, incomprehensibility, numbness, blame, and low consensus—accounted for 18.2% of the variance in BED. Additionally, important findings emerged for BP, where incomprehensibility, non-acceptance of feelings and simplistic view of emotion accounted for 5.8% of the variance. Additionally, the Arabic adaptation of the BPS demonstrated robust psychometric properties and confirmed a two-factor structure consistent with previous cultural adaptations. Conclusion: These findings underscore the necessity of addressing emotional schemas in therapeutic interventions to reduce BED and BP. Furthermore, the validated Arabic BPS offers a vital tool for future research and assessment in Arabic-speaking contexts.